2020
DOI: 10.15586/qas.v12i3.716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan treatment on the texture parameters of okra fruit (Abelmoschus esculentus L. Moench)

Abstract: In recent years, due to its medicinal properties and reputation as a healthy vegetable, consumption of okra (Abelmoschus esculentus L.) has considerably increased in China. In this study, texture parameters (hardness, springiness, cohesiveness, gumminess, chewiness, and resilience) of okra fruit subjected to chitosan (CTS) treatment and control were determined during storage. The changing pattern of texture properties and the differences between three different cultivars (Kariba, ACF, and Xianzhi) were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This demonstrates that NCC can be used to improve fruit preservation in place of using chemical preservatives. Our previous research (Wang et al, 2020) showed that okra fruit texture is significantly influenced by CS coating. In this study, we investigated the effect of CS-NCC coating on okra fruit during storage in order to improve the preservation effect of CS on the fruit.…”
Section: Change In Fruit Decay Rate During Storagementioning
confidence: 99%
See 2 more Smart Citations
“…This demonstrates that NCC can be used to improve fruit preservation in place of using chemical preservatives. Our previous research (Wang et al, 2020) showed that okra fruit texture is significantly influenced by CS coating. In this study, we investigated the effect of CS-NCC coating on okra fruit during storage in order to improve the preservation effect of CS on the fruit.…”
Section: Change In Fruit Decay Rate During Storagementioning
confidence: 99%
“…The coating treatment was implemented according to a previously reported method (Wang et al, 2020). Samples were soaked for 2 min; air-dried; wrapped in a plastic bag; and stored at -10°C in a refrigerator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of chitosan in food and pharmaceutical products is mainly seen due to its unique bioactivities and functional properties [7]. Besides, its antimicrobial potential has other interesting characteristics, including antioxidant activity, lipid binding, water-holding capacities, and emulsifying properties [8,9]. Chitosan has illustrated considerable potential to enhance meat products' technological and nutritional quality [10,11].…”
Section: Introductionmentioning
confidence: 99%